Fatigue crack growth behavior of NBR, HNBR, HNBR ZSC compounds. (2018) - Béranger, A.S.; Qin, J.; Heuillet, P.; Baurier, H.
Abstract: Due to the insufficiency of reliable data, fatigue life calculations taking the crack propagation phenomena into account, remain scarce. Therefore, this work focuses on the characterization of fatigue crack growth behavior for materials NBR, HNBR and HNBR ZSC in different thermal ageing states at different temperatures. The experimental data base was analyzed using Fracture Mechanics principles, namely crack growth rate in relation with the tearing energy. The tests of the notched pure-shear specimen were performed on a METRAVIB DMA+300 fatigue testing machine. It is found that the crack growth rate is approximately proportional to the tearing energy in the steady propagation range. Furthermore, the test temperature and thermal ageing were observed to be able to weaken the shearing strength.